Space without scales: Established/outsider relations in Hérouxville - Nieguth, Tim; Lacassagne, Aurélie (Culture and Local Governance / Culture et gouvernance locale, 2012)
In 1965, Norbert Elias and John Scotson published a seminal study on the dynamics of established/outsider relations. Their analysis has been criticized on several grounds, including its relative inattention to space. A number of recent studies have sought to build on Elias and Scotson's model by putting greater emphasis on space. These studies represent important interventions in the development of a relational approach to local established/outsider relations. Nonetheless, such an approach would benefit from further refinement. In particular, an Eliasian approach can be especially valuable to the study of local power relations and identity constructions if it takes into account the overlapping nature of configurations, emphasizes that individuals are simultaneously embedded in a large number of configurations, recognizes that different spatial contexts are not merely external resources to be manipulated by (local) actors, and refuses to treat conflicts that happen to play out in local contexts as purely local phenomena.